Ergonomic principles and usability augmented reality interfaces in virtual learning environments: overview and trends - Vaghetti, César Augusto Otero (2010)
The objective of this research was to present a revision of recent researches involving ergonomics and usability in environments of mixed reality. The challenges associated to the future of virtual environments of training that arise with those technologies and what computational, educational and ergonomics resources should be implemented, were investigated. The bibliographical revision was carried out through the search in three service of index-linking in the Web, indicate that few researches utilize technologies of increased and mixed reality with emphasis in the educational aspects.